Integration of Instructional Leadership and Ethnopedagogy: Strategies to Improve Learning Quality in Higher Education - Siregar, Martua; Lubis, Fitri Romaito; Harahap, Yusniar; Nasution, Sarip Parmohonan; Siregar, Helmi Suryana (Jurnal Komunikasi Pendidikan, 2025)
Integrating modern leadership approaches with local wisdom remains a challenge in enhancing the quality of education in Indonesian higher education institutions. This study examines the impact of integrating instructional leadership with ethnopedagogy based on the Dalihan Na Tolu philosophy on learning quality at Graha Nusantara University. Using a mixed-method approach with a sequential explanatory design, the study involved 50 lecturers selected through systematic random sampling and 100 students. Data were collected through validated questionnaires (validity coefficients ranging from 0.72 to 0.89; reliability with Cronbach's Alpha of 0.88), in-depth interviews, and participatory observations. The findings reveal that instructional leadership independently accounts for 67 percent of the variation in learning quality (coefficient of determination, R-squared = 0.670, with p < 0.001), with key determinants being guidance (correlation coefficient = 0.820) and vision-mission communication (correlation coefficient = 0.790). Ethnopedagogical leadership contributes significantly through the values of Somba Marhula-hula (regression coefficient = 0.45), Manat Mardongan Tubu (regression coefficient = 0.41), and Elek Marboru (regression coefficient = 0.38). The integration of these approaches produces significant synergistic effects (R-squared = 0.830), resulting in a 70 percent increase in active interaction, a 68 percent improvement in the effectiveness of learning strategies, and a 66 percent boost in productivity. This study contributes to developing an integrated leadership model that combines modern values with local wisdom. It also provides practical implications for designing training programs and implementing dual-approach monitoring systems in higher education institutions.